(untitled) (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of people aged 50 years or older living with the human immunodeficiency virus, in Roraima, Brazil. Methodology: This is a descriptive, cross-sectional, population-based observational study, using secondary data from individuals aged 50 years or older with HIV/AIDS in Roraima notified in Sinan, from 2010 to 2019. Results: 342 cases of HIV/AIDS were reported in in this age group in Roraima (10.4% of the total of 3277 cases registered among all population groups). The cases occurred mainly in brown-skinned individuals, with low education, whose most frequent occupations were housewife, retiree/pensioner, prospector and agricultural worker. The main route of exposure to HIV was heterosexual. The age group with the highest incidence was 50 to 59 years old (72.8%), with a predominance of males (64.6%). Regarding the staging of the syndrome, 199 (58.2%) of the individuals evaluated had manifest AIDS at the time of notification of the case. As for the country of origin, a significant increase was observed in the number of notifications in patients from Venezuela (p<0.05). Conclusion: Data from the last decade showed, in Roraima, a profile of people with HIV with sociodemographic and clinical characteristics peculiar to the local reality. The data presented can support interventions in public health, as well as support future investigations in this field still insufficiently studied.